Separation of Protein Crystals from Spores of Bacillus thuringiensis by Ludox Gradient Centrifugation - Zhu, Yu Sheng (1989)
A method is described for the purification of Bacillus thuringiensis protein crystals by Ludox gradient centrifugation. This method is simple, inexpensive, fast, and efficient compared with other techniques. It has been successfully used to purify and characterize the protein crystals from several B. thuringiensis strains.